Analysis and design of smart paper punching machine for spiral binding. (2020) - Sathish, T.; Sabarirajan, N.; Karthick, S.
Abstract: In this study mainly concentrated on the automation method to produce new equipment. The Paper punching machine is one of the important equipment for to make holes for spiral binding process. The existing mechanism is a difficult one to form a hole based on the increasing of paper count, much more human effort is also needed. This study and design is to improve the equipment in the sense of automation, the automation help to improve spiral binding works with produce bulky spiral binding in the short period and also reduce the human effort. In this study replacing of pedal operated mechanism and introduces electric motor with drive mechanism, reduction gear box and cam mechanism.